Microenvironmental signals shaping NK-cell reactivity in cancer: review - Balzasch, Bianca M.; Cerwenka, Adelheid (European journal of immunology, 2023)
Since the postulation of the “missing-self” concept, much progress has been made in defining requirements for NK-cell activation. Unlike T lymphocytes that process signals from receptors in a hierarchic manner dominated by the T-cell receptors, NK cells integrate receptor signals more “democratically.” Signals originate not only the downstream of cell-surface receptors triggered by membrane-bound ligands or cytokines, but are also mediated by specialized microenvironmental sensors that perceive the cellular surrounding by detecting metabolites or the availability of oxygen. Thus, NK-cell effector functions are driven in an organ and disease-dependent manner. Here, we review the latest findings on how NK-cell reactivity in cancer is determined by the reception and integration of complex signals. Finally, we discuss how this knowledge can be exploited to guide novel combinatorial approaches for NK-cell-based anticancer therapies.